Enhancing Tax Compliance in Indonesian Government Institutions: Identifying and Mitigating Inhibiting Factors - Silalahi, Heriantonius (Yayasan Ilomata, 2024)
Tax compliance in Indonesian government institutions significantly affects national revenue and resource allocation. This study addresses tax non-compliance by identifying its causes and proposing mitigation strategies. The research aims to understand why government institutions in Indonesia struggle with tax compliance, with objectives including identifying inhibiting factors, assessing their impact, and proposing mitigation strategies. This integrated approach encompasses various elements, including a descriptive analysis approach, comprehensive literature research, comparative analysis, a qualitative research approach, and secondary data collection. Findings highlight complex regulations, inadequate tax education, and inconsistent enforcement as compliance hindrances. The study quantifies their impact. Proposed solutions include simplifying tax rules, enhancing tax education, and enforcing tax laws. In conclusion, this research informs policymakers, tax authorities, and government officials about tax compliance challenges, offering insights to improve tax collection and resource allocation, potentially increasing government revenue and promoting sustainable development.